The Influence Of Number Head Together Learning With Intelligent Puzzle On Mathematics Learning Out Comes - Fadhilla, Nuansa Trimaya; Hamdi, Syukrul (PT. BATARI EDU CALYA, 2024)
This research aims to determine the influence of number heads together learning with intelligent puzzle on mathematics learning outcomes on grade IV students of Kepatihan Primary school Purworejo City. This research method is quasi experimental with Nonequivalent Group Pretest Posttest Design. Sample selected by using saturated sampling. The population of this research is all Grade IV students of Kepatihan Primary School Purworejo. Class IV A (21) as control class, and class IV B (18) as experimental class. Data analysis includes validity, normality, homogeneity test and Mann-Whitney U test with the help of SPSS 23 Program. The results of this research show there is influence of number heads together learning with intelligent puzzle on mathematics learning outcomes on grade IV students of Kepatihan Primary School Purworejo. The result of this research shows Asymp.Sig (2tailed) 0.001 < 0.05. Based on the results of the analysis and discussion, there is a difference in the mean score of learning outcomes experimental class is 94.90 and control is 81.21.